Biophotonic implants for NIR-imaging - Antonova, Natalia (My University, 2025)
Bioactive glasses (BAGs) are implantable biomaterials that promote bone tissue regeneration and healing. Various radiographic imaging techniques are commonly used to monitor the state of BAGs after implantation. However, due to the weak contrast between the biomaterial and bone tissue, the information obtained from radiographic images is limited. The fabrication of biophotonic BAGs by doping phosphor materials into a glass matrix allows the use of optical imaging techniques or combinations of imaging techniques for the non-invasive real-time monitoring of implants. During optical imaging, light encounters various photophysical processes, such as reflection, scattering, and absorption, when it passes through biological tissues, which significantly reduce its intensity. However, NIR light is the least susceptible to these processes. Therefore, today, the primary challenge for researchers is the development and fabrication of phosphors with the desired optical properties in the NIR region. During this work, MgO and Mg14Ge5O24 NIR phosphors doped with both rare earth and transition metal ions were synthesized. Samples with the best NIR optical properties were selected and doped into a NaPSrO glass matrix. The fabricated glass-phosphor composites demonstrated promising results, indicating that they can be used as biophotonic implants for NIR optical imaging.
Keywords: bioactive glass, biophotonic implants, NIR optical imaging, NIR-phosphors, doped MgO, doped Mg14Ge5O24, 3D scaffolds, glass-phosphor composites